Crossover Alternatives of Default Right Radial Artery Access for Acute Myocardial Infarction Intervention - Kalpak, Oliver; Pejkov, Hristo; Kalpak, Gjorgji; Jovanoska, Marija; Zafirovska, Biljana; Kedev, Sashko (Macedonian Medical Association/ Walter de Gruyter GmbH, 2017)
Abstract. Introduction.Being a default transradial access center we have encountered the need for alternative to the right radial artery. Determining the most frequent alternative access strategy for PCI in STEMI patientswasthe focus of our study. We sought to analyze whether the wrist access strategy impacts procedure time and success rate particularly for the STEMI interventions where time is of paramount importance. Methods. During four years, in our Center 2624 consecutive all-comers STEMI patients underwent urgent coronary intervention. TRA was used as the first-choice access strategy. We sought to assess crossover rate and safety of preferable access strategy. Crossover occurred according to the operator's decision. Primary outcomes were: access site crossover rate and In Lab time, secondary outcomes were PCI time, X-ray time, mortality and MACE at 30 days and at 6 months. Results. Overall crossover rate from default radial was 5.4% (144 out of 2624 patients). We treated 98.7% (2589) patients by wrist access and only 1.3% (35) patients with TFA. Crossover towards left radial occurred in 47.9% (69 out of 144 patients), towards ulnar 27.8% (40 patients) and towards TFA only 24.3% (35 patients). The meanIn-Lab time 40.4±17.7 minutes, PCI time was 21.4±7.4 min, X-ray time 9.2±4.7 minutes. Survival outcomes at 30 days were: MACE rate of 6.6% (174 patients), mortality rate of 5.0% (131 patients). At six months MACE rate was 8.6% and mortality rate was 5.6%. Conclusions. Default radial access is associated with alow crossover rate. Crossover towards femoral occurred less frequent than ulnar artery access.Complete wrist access strategy is safe and feasible for STEMI interventions with low mortality and MACE rate in unselected all-comers cohort.
АЛТЕРНАТИВИ НА РАДИЈАЛНИОТ АТЕРИСКИ ПРИСТАП ЗАИНТЕРВЕНЦИЈА ПРИ АКУТЕН МИОКАРДЕН ИНФАРКТ